Concepts for Contemporary Social Work: Globalization, Oppression, Social Exclusion, Human Rights, Etc. - Katherine van Wormer (Social Work and Society)
The society wrestles with mass social change congruent with economic globalization and the communications revolution. This change creates new challenges for the social work profession in the areas of social and economic justice. This article analyzes the terminology of the new global era, words that signify a paradigm shift in outlook, most of them a reaction to the new authoritarianism of the age. Globalization, oppression, social exclusion, human rights, harm reduction, and restorative justice are the representative terms chosen.